Synthesis and properties of novel multiblock copolyimides consisting of benzimidazole-groups-containing sulfonated polyimide hydrophilic blocks and non-sulfonated polyimide hydrophobic blocks as proton exchange membranes. (20th September 2015) - Guo, Xiaoxia; Li, Wei; Fang, Jianhua; Yin, Yan
Abstract: A series of novel multiblock copolymers consisting of benzimidazole-groups-containing sulfonated polyimide hydrophilic blocks (averaged block length = 20) and non-sulfonated polyimide hydrophobic blocks (averaged block length = 5 or 10) have been synthesized via two-pot synthetic procedures. The anhydride-terminated hydrophilic oligomer is synthesized by copolymerization of excess 1, 4, 5, 8-naphthalelnetetracarboxylic dianhydride (NTDA) with amine-terminated polybenzimidazole (PBI-NH2 ) and 4, 4′-bis(4-aminophenoxy) biphenyl-3, 3′-disulfonic acid (BAPBDS), while the amine-terminated hydrophobic oligomers are synthesized by polymerization of excess non-sulfonated diamines with NTDA or a fluorinated dianhydride. The resulting multiblock copolymers can be cast into tough membranes indicating that reasonably high molecular weights block copolymers have been obtained. The block SPIs exhibit microphase-separated structure, whereas the random one is amorphous. Fenton's test reveals that the block copolymer membranes, in particular, those consisting of fluorinated hydrophobic blocks, are fairly stable toward radical oxidation. Preliminary fuel cell tests are performed to evaluate the fuel cell performance of the block copolymer membranes. The single cell equipped with the block copolymer membrane of which hydrophobic block is prepared from NTDA and a fluorinated diamine (averaged block length = 5) exhibits a peak output power density of 0.70 W/cm 2 at 90 °C and 92% relative humidity for H2 /air which is comparable to that of Nafion 112.